2002
DOI: 10.1126/science.1068712
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Pathway Stimulated by the Forkhead Transcription Factor FOXO3a Through the Gadd45 Protein

Abstract: The signaling pathway from phosphoinositide 3-kinase to the protein kinase Akt controls organismal life-span in invertebrates and cell survival and proliferation in mammals by inhibiting the activity of members of the FOXO family of transcription factors. We show that mammalian FOXO3a also functions at the G2 to M checkpoint in the cell cycle and triggers the repair of damaged DNA. By gene array analysis, FOXO3a was found to modulate the expression of several genes that regulate the cellular response to stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
607
2
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 770 publications
(633 citation statements)
references
References 19 publications
14
607
2
5
Order By: Relevance
“…Therefore, the difference of Gadd45a expression in MEFs isolated from E14.5 embryos is discernible, but becomes obvious in tissues from 6-month-old WT and TR4KO mice. It has been shown that FOXO3a can directly up-regulate the expression of Gadd45a during genotoxic stress [24]. Here, we find that IR poorly induces Gadd45a expression in TR4KO cells and TR4 can directly regulate transcription of Gadd45a .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, the difference of Gadd45a expression in MEFs isolated from E14.5 embryos is discernible, but becomes obvious in tissues from 6-month-old WT and TR4KO mice. It has been shown that FOXO3a can directly up-regulate the expression of Gadd45a during genotoxic stress [24]. Here, we find that IR poorly induces Gadd45a expression in TR4KO cells and TR4 can directly regulate transcription of Gadd45a .…”
Section: Discussionsupporting
confidence: 57%
“…By using DNA Damage Signaling Pathway focused PCR Array (SABiosciences ™ ), we found that expression of several genes controlling cell cycle arrest, including Gadd45a (growth arrest and DNA-damage-inducible, alpha), was reduced in TR4 knockdown cells (data not shown). Gadd45a is reported to be induced by multiple types of genotoxic stress including ultraviolet radiation and ionizing radiation (IR) [22, 23], and is downstream of the FOXO3a stimulated DNA repair pathway when cells are exposed to genotoxic stress [24]. We therefore suggest that TR4 is the mediator through which FOXO3a regulates GADD45A to promote DNA repair and protect cells from IR-induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, ectopic overexpression of tamoxifen‐inducible forms of FOXO1 (FOXO1‐ER) or FOXO3 (FOXO3‐ER) in human immortalized NP cells (Sakai et al, 2004) increased mRNA levels of SESN3 , MAP1LC3 , GABARAPL1 , and PRKAA2 (Figure 5f). This transcriptional activation of homeostatic genes was likely a direct function of FOXO as overexpression of a FOXO3 mutant that lacks the DNA binding region (FOXO3‐∆DBD‐ER) (Tran et al, 2002) did not change gene expression (Supporting information Figure S8 in Appendix S1). In addition, LC3‐II levels were significantly elevated in cells overexpressing FOXO1 or FOXO3 (Figure 5g), indicating that FOXO is sufficient to stimulate autophagy in NP cells.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the MyD/Gadd (growth arrest and DNA damage response) gene family function to regulate transcription and cell proliferation (Zhan et al, 1994). Gadd45 is a DNA damage-responsive gene that occurs in three isoforms (a, b, and g) and functions in DNA repair, cell cycle checkpoint mechanisms, and apoptosis pathways (Kastan et al, 1992;Jin et al, 2000b;Sheikh et al, 2000;Tran et al, 2002). Several studies suggest that BRCA1 up-regulates the expression of Gadd45 (¼ Gadd45a), in part, by activating the Gadd45 promoter (Harkin et al, 1999;Jin et al, 2000a).…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%